2018
DOI: 10.1007/s13595-018-0717-7
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of carbon accumulation in Eucalyptus and Acacia plantations in the Pearl River delta region

Abstract: & Key message Plantation type and age strongly influence the quantity of carbon stored in forest ecosystems. The marked increase in total ecosystem carbon stock achieved over time by the Eucalyptus and Acacia plantations has confirmed that the afforestation of degraded soils can contribute positively to carbon sequestration. & Context Reforestation has been widely conducted to restore and protect the eroded red soil in south China in recent decades. The question as to whether the content of soil organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
4
14
0
4
Order By: Relevance
“…Our results add to these studies by demonstrating that successful soil restoration could be obtained within two decades, at least in some tropical environments [56]. These results suggest that there is no universal global period for soil restoration, with significant differences depending on the specific context of each ecosystem, such as climatic conditions, surrounding vegetation, the origin of the disturbance, and the restoration approach [22,56,57,67]. Focusing on soil restoration, our results enable us to support afforestation after soil amendments as a critical catalyst for restoring soil properties after mining.…”
Section: Influence Of Restoration Interventions On Soil Attributessupporting
confidence: 53%
“…Our results add to these studies by demonstrating that successful soil restoration could be obtained within two decades, at least in some tropical environments [56]. These results suggest that there is no universal global period for soil restoration, with significant differences depending on the specific context of each ecosystem, such as climatic conditions, surrounding vegetation, the origin of the disturbance, and the restoration approach [22,56,57,67]. Focusing on soil restoration, our results enable us to support afforestation after soil amendments as a critical catalyst for restoring soil properties after mining.…”
Section: Influence Of Restoration Interventions On Soil Attributessupporting
confidence: 53%
“…In the three age-sequence A. mangium stands of this study, the SOC concentration was the highest in the surface 0-10 cm soil layer and revealed a decreasing trend with increasing depth (Figure 2a). The SOC produced from the decomposition of root system and litter near the ground surface will get into the topsoil first, this could be responsible for the significant higher SOC content in the upper soil layer (Zhong and Qiguo, 2001;He et al, 2009;Laik et al, 2009;Thanh and Cuong, 2017a;Zhang et al, 2018). The concentration of C stored in the top three soil layers (0-10 cm, 10-20 cm, and 20-30 cm) and the deepest layer (30-50 cm) significantly increased with increased age of A. mangium plantations, probably due to the increase of litter productivity and slow decomposition in older stands (Herdiyanti and Sulistyawati, 2009;Ming et al, 2014).…”
Section: Soil Organic Carbon Content and Storage In A Mangium Plantat...mentioning
confidence: 99%
“…Whereas others showed an increasing SOC in the early period after afforestation followed by a gradual decrease (Ali et al, 2019;Zhang et al, 2019), a stable SOC after afforestation (Simon et al, 2012), or no significant increase with stand development (Matthias and Arain, 2006;Yue et al, 2018). Nonetheless, according to most researches, SOC significantly increased with forest age (Cheng et al, 2015;Zhang et al, 2018). One possible interpretation to this discrepancy is that, in addition to stand age, several other factors impact SOC accumulation, such as tree species, forest types, climate conditions, soil physicochemical characteristics, and former land use (Smal and Olszewska, 2008;Noh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zhang et al (2019a) found that restoration type and soil depth were the two most important factors contributing to SQI of vegetation restoration in degraded karst areas. In addition, restoration time played a non-negligible role in VSQI, due mainly to ecosystem carbon stock sequestration achieved over time as a result of vegetation restoration (Zhang et al 2018a), since soil organic matter/carbon is the key factor to determining soil quality (Bunemann et al 2018). In conclusion, vegetation restoration type is the dominant factor that affects soil quality and the longer restoration time achieves the better restoration effects.…”
Section: Analysis Of the Effects Of Different Vegetation Restoration Types On Soil Qualitymentioning
confidence: 99%